Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films: first-principle DFT computations supporting the systematic experimental endeavor - Sharma, Vidhika; Dixit, Mudit; Satsangi, Vibha R.; Dass, Sahab; Pal, Sourav; Shrivastav, Rohit (International Journal of Hydrogen Energy, 2014)
Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films was investigated. ZnO thin films with 1, 3, 5 and 7% at. Mn incorporation were synthesized by sol gel method and characterized by X-Ray Diffraction (XRD) analysis, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), X-ray Photoelectron spectroscopy (XPS), High Resolution Transmission Electron Microscopy (HR-TEM) and UV-Vis spectroscopy. Mn incorporation coupled with variation in sintering temperature led to significant microstructural changes, which tentatively influenced the magnitude of optical absorption and charge carrier mobility, thereby impacting the performance of such systems towards photoelectrochemical splitting of water. Electronic structure computations based on first principle density functional theory (DFT) revealed electronic states of Mn being responsible for the marginally recorded red shift in bandgap energy. Photoelectrochemical measurements using thin films of 1% at. Mn:ZnO sintered at 600 degrees C yielded 3 times enhanced photocurrent at zero bias due to improved optical absorption. Plausible explanations for the effect have also been offered. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Hydrogen energy; Mn doped ZnO; Optical properties; Photoelectrochemical water splitting